Influence of Coarse Aggregate Gradation on the Mechnical Properties of Concrete, Part I: No-Fines Concrete - Tunio, Z. A.; Abro, F. U. R.; Ali, T.; Buller, A. S.; Abbasi, M. A. (Engineering, Technology & Applied Science Research, 2019)
It is well-accepted fact that in concrete construction, the self-weight of the structure is a major part of its total load. Reduction in the unit weight of the concrete results in many advantages. The structural lightweight aggregate concrete (LWAC) of adequate strength is now very common in use. In frame structures, the partition walls are free of any loading, where the construction of these non-structural elements with lightweight concrete of low strength would lead to the subsequent reduction of the overall weight of the structure. No-fines concrete is one of the forms of lightweight concrete and it is porous in nature. It can be manufactured similarly as normal concrete but with only coarse aggregates and without the sand. Thus, it has only two main ingredients; the coarse aggregates and the cement. The coarse aggregates are coated with a thin cement paste layer without fine sand. This is a detailed experimental study carried on NFC with fixed cement to the aggregate proportion of 1:6 with w/c 0.40 ratio. In this study, coarse aggregate of various gradations (7-4.75) mm, (10-4.75) mm, (10-7) mm, (13-4.74) mm, (10-7) mm, (13-4.75) mm, (13-10) mm, (13-7) mm, (20-4.75) mm, (20-7) mm, (20-10) mm, (20-13) mm, are used, where prefix and suffix show the maximum and minimum size of the aggregate. The cube and cylinder specimens of standard sizes are cast to determine the compressive strength and splitting tensile and the specimens are cured in water up to the age of testing (28 days).